Analisis Implementasi Rekam Medis Elektronik terhadap Kelengkapan Dokumentasi Rekam Medis - Purnamasari, Novita; Bachtiar, Adang (UI Scholars Hub, 2025)
Completeness of medical records is one of the important factors in improving the quality of health services. Despite its importance, incomplete documentation remains a prevalent issue, and the adoption of Electronic Medical Records (EMRs) is anticipated to address this challenge. This study is a narrative review and utilized the PRISMA 2020 flow diagram for literature selection. Articles were sourced from the ProQuest and Scopus databases for articles published in 2019-2024. From an initial selection of 431 articles, eight articles met the inclusion criteria for this study. The analysis of these studies shows that the implementation of electronic medical records positively influences the medical record documentation’s completeness. Among the eight reviewed articles, seven articles demonstrated significant improvements in the completeness of medical documentation following electronic medical record implementation. Continuous evaluation and identification of supporting factors for implementing electronic medical records in improving medical record documentation’s completeness need to be studied further.